1991
DOI: 10.1007/bf00219448
|View full text |Cite
|
Sign up to set email alerts
|

Cytological analysis on the distribution and origin of the alien chromosome pair conferring blue aleurone color in several European common wheat (Triticum aestivum L.) strains

Abstract: Meiotic chromosome pairing and Giemsa C-banding analyses in crosses of several European blue-grained wheat strains with Chinese Spring double ditelosomic and other aneuploid lines showed that Triticum aestivum Blaukorn strains "Berlin," "Probstdorf," "Tschermak," and "Weihenstephan" are chromosome substitutions, in which the complete wheat chromosome 4A pair is replaced, whereas the strains "Brünn" and "Moskau" are 4B substitutions. The alien chromosome pair in all of these strains is an A genome chromosome (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…The gene for blue aleurone was transferred from the tall wheatgrass Agropyron elongatum to bread wheat (Triticum aestivum L.) (Zeller et al 1991;Morrison et al 2004). Similarly, translocation lines of the tall wheatgrass Thinopyrum ponticum with the blue aleurone gene(s) have also been characterised (Zheng et al 2006).…”
Section: Anthocyanin Pigment: Composition and Distribution Along The mentioning
confidence: 99%
“…The gene for blue aleurone was transferred from the tall wheatgrass Agropyron elongatum to bread wheat (Triticum aestivum L.) (Zeller et al 1991;Morrison et al 2004). Similarly, translocation lines of the tall wheatgrass Thinopyrum ponticum with the blue aleurone gene(s) have also been characterised (Zheng et al 2006).…”
Section: Anthocyanin Pigment: Composition and Distribution Along The mentioning
confidence: 99%
“…In the German language blaukorn literally means blue grain. The breeding history of the various lines according to Zeller et al (1991) Cermeno & Zeller (1988), who showed that Blaukorn Berlin, Blaukorn Tschermak and Blaukorn Probstdorf were substitution lines in which chromosome pair, 4A a from T. aestivum is replaced by chromosome pair 4A b° of Triticum boeoticum or T. monococcum. The same holds for Blaukorn Weihenstephan.…”
Section: Received Seedsmentioning
confidence: 99%
“…Zeller (1976) suggested the blue-grain colour of Blaukorn W70a86, could derive from a species other than rye. He and his co-workers finally concluded that it 'possesses, in addition to a rye chromosome pair 5R compensating for the loss of part of chromosome 5D, a 4A/5DL translocation replacing chromosome 4B of wheat' (Zeller et al, 1991).…”
Section: Received Seedsmentioning
confidence: 99%
See 2 more Smart Citations